Experimental and Numerical Investigations on Conductive Drying of Phosphate Washing Waste Clay - Fatiha Berroug (Minerals, 2021)
Morocco is the leading producer of phosphate and its derivatives in the world with a total production of 35 Mt. However, the extraction and the valorization of this mine generate huge quantities of phosphate washing waste clay (PHWWC) that constitute a main environmental and economic concern. To facilitate this waste clay storage and handling, it is necessary to decrease its moisture content that represents 80% of PHWWC. The present paper is devoted to studying the conductive drying of PHWWC. Drying experiments were conducted in a laboratory pilot. Afterwards, the experiment results were implemented in a one-dimensional numerical model of heat and mass transfer in a porous media to identify the drying parameters and performances. It was found that most of the water contained in PHWWC is free water that is removed with a constant drying rate. The volume reduction with a marked cracks phenomenon attained 65% without any significant effect of drying temperature and sample thickness. The effective moisture diffusivity of the PHWWC for a conductive drying process is ranged between 10−9 and 1.1 × 10−8 m2·s−1. The thermal efficiency of the drying system is up to 86%. The results could be used for the purpose of design and scale-up of the industrial dryer based on laboratory-scale experiments.